2018
DOI: 10.1007/s11356-018-1796-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of physicochemical properties of 2-ethylhexyl-4-methoxycinnamate (EHMC) degradation products and their toxicological evaluation

Abstract: The organic UV filters, commonly used in personal protection products, are of concern because of their potential risk to aquatic ecosystems and living organisms. One of UV filters is ethylhexyl-4-methoxycinnamate (EHMC) acid. Studies have shown that, in the presence of oxidizing and chlorinating factors, EHMC forms a series of products with different properties than the substrate. In this study, the toxicities of EHMC and its transformation/degradation products formed under the influence of NaOCl/UV and H2O2/U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…EHMC is not only widely distributed in aquatic environments but also accumulates in aquatic organisms [26,27]. It has been reported that EHMC and its degradation products shown high ecological toxicity [28]. According to our previous studies, it is found that antibiotics and OUVFs occurred and were widely occurrence and distributed in the Yarlung Zangbo River.…”
Section: Introductionmentioning
confidence: 95%
“…EHMC is not only widely distributed in aquatic environments but also accumulates in aquatic organisms [26,27]. It has been reported that EHMC and its degradation products shown high ecological toxicity [28]. According to our previous studies, it is found that antibiotics and OUVFs occurred and were widely occurrence and distributed in the Yarlung Zangbo River.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies demonstrated that UV filters could undergo photoinduced modifications that could alter their toxicity. BP3 displayed phototoxicity on human skin cells (Kim et al, 2018) and the UV-exposed EHMC showed an enhanced toxicity to Aliivibrio fischeri, Daphnia magna and Artemia salina (Gackowska et al, 2018). In this study, two strategies were used to investigate the combined effect of solar radiation and UV filters: (i) indirect effects: bacterial viability was monitored in the dark with UV filters previously exposed to solar radiation during 5 h (Figs.…”
Section: Combined Effect Of Solar Radiation and Uv Filtersmentioning
confidence: 99%
“…Green line indicates 5% of sludge, red line indicates 10% of sludge, and blue line indicates 20% of sludge Gago-Ferrero et al (2011), biodegradation processes of ODPABA in the sewer and during wastewater and/or sludge treatment cannot be ruled out. Moreover, our previous studies have shown that EHMC and ODPABA transform under influence of oxidising agents with formation of products significantly more toxic than the substrates themselves (Studziński et al 2017;Gackowska et al 2018). In order to verify whether biochemical transformations of UV filters occur under the influence of activated sludge, studies were carried out on model systems.…”
Section: Effect Of Activated Sludge On Removal Of Uv Filters From Wasmentioning
confidence: 99%
“…It may be due to the fact that it is a hydrophilic compound (log K ow 2.73), which migrates to water and is not absorbed in the soil, log K oc 1.415. The mentioned products are also formed under the influence of oxidising and chlorinating agents (Gackowska et al 2016(Gackowska et al , 2018.…”
Section: Effect Of Activated Sludge On Removal Of Uv Filters From Wasmentioning
confidence: 99%